Interference study between wireless microphone systems and TV white space devices - Dionísio, Rogério Pais (2012)
This work focus on a coexistence study between wireless microphone systems and secondary users of the TV White Spaces, using a Monte-Carlo methodology. Exclusion areas around wireless microphone receivers, for co-channel and adjacent channel interference, are computed, considering indoor and outdoor scenarios. Using this methodology, impact and tendencies of several parameters over the probability of interference are analyzed, like spectral channel spacing, separation distance and propagation scenario. As an example, for outdoor scenarios, the spectral spacing between primary system and secondary users, ranging from 0 MHz (co-channel operation) to 16 MHz (2 DVB-T channels) results in a protection distance of 13.9 km and 2.2 km, respectively.